2017
DOI: 10.1002/ijgo.12385
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of ectopic pregnancy after hysterectomy

Abstract: A high index of suspicion and a low threshold for performing a β-hCG pregnancy test is recommended in all women presenting with clinical symptoms of ectopic pregnancy, regardless of the hysterectomy status. This could lead to earlier diagnosis and fewer complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Although tubal disruption techniques (electrical, surgical and mechanical) have traditionally been the most common techniques for permanent contraception [3,4], total BS has gained popularity with a significant increase in performed procedures over the last decade [3,9,[18][19][20]. Pregnancy after tubal disruption techniques, ectopic pregnancy after hysterectomy and ectopic pregnancy after assisted reproductive technology following total BS has been reported [2,21,22]. A systematic review of ectopic pregnancy after hysterectomy described 57 pregnancies in the past 72 years [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tubal disruption techniques (electrical, surgical and mechanical) have traditionally been the most common techniques for permanent contraception [3,4], total BS has gained popularity with a significant increase in performed procedures over the last decade [3,9,[18][19][20]. Pregnancy after tubal disruption techniques, ectopic pregnancy after hysterectomy and ectopic pregnancy after assisted reproductive technology following total BS has been reported [2,21,22]. A systematic review of ectopic pregnancy after hysterectomy described 57 pregnancies in the past 72 years [21].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy after tubal disruption techniques, ectopic pregnancy after hysterectomy and ectopic pregnancy after assisted reproductive technology following total BS has been reported [2,21,22]. A systematic review of ectopic pregnancy after hysterectomy described 57 pregnancies in the past 72 years [21]. Similarly, a review of the literature described 20 cases of ectopic pregnancy following in vitro fertilization following total BS [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that many of these patients who present soon after the hysterectomy procedure are often diagnosed with postoperative complications leading to a delay in the diagnosis of ectopic pregnancy. 4 …”
Section: Discussionmentioning
confidence: 99%
“…This diagnosis is often challenging as presenting symptoms are non-specific. There have been multiple reported cases in the literature of ectopic pregnancies occurring post hysterectomy, 1 , 4 , 8 , 16 with the majority occurring during the time interval directly following the procedure. 1 This case demonstrates how point-of-care ultrasound (POCUS) helped to diagnose a patient with a post-hysterectomy ectopic pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A histerectomia total é o procedimento cirúrgico realizado por via abdominal e/ou vaginal, que remove a totalidade uterina, culmina com a fixação e síntese integral da cúpula vaginal com os ligamentos uterinos, sem restar quaisquer pontos e/ou áreas de comunicação entre a vagina e a cavidade peritoneal. 1 Os seguimentos pós-operatórios destas pacientes podem ser longamente assintomáticos, porém, queixas e/ou raras complicações tardias na cúpula vaginal isoladas ou associadas entre si, podem surgir, como: hematomas, granulomas, queloides, herniação, formações vasculares, 2, 3 endometriose, 3 infecções focais, 4 gestação abdominal, 5 neoplasias 6 e/ou fístulas tardias entre a cavidade peritoneal e a cúpula vaginal. 3,4,6,7 A ocorrência de sangramentos irregulares ou cíclicos semelhantes a fluxos menstruais, nestas pacientes histerectomizadas são raros, podendo surgir meses ou anos após a cirurgia bem-sucedida.…”
Section: Introductionunclassified